2014
DOI: 10.1124/dmd.114.060186
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD28 Monoclonal Antibody–Stimulated Cytokines Released from Blood Suppress CYP1A2, CYP2B6, and CYP3A4 in Human Hepatocytes In Vitro

Abstract: Like most infections and certain inflammatory diseases, some therapeutic proteins cause a cytokine-mediated suppression of hepatic drug-metabolizing enzymes, which may lead to pharmacokinetic interactions with small-molecule drugs. We propose a new in vitro method to evaluate the whole blood-mediated effects of therapeutic proteins on drug-metabolizing enzymes in human hepatocytes cocultured with Kupffer cells. The traditional method involves treating hepatocyte cocultures with the therapeutic protein, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Indirect, cytokine-mediated, suppression of mRNA and reduction in enzyme activity of CYP1A2 and CYP3A4 by plasma from blood treated with LPS were expected. 18,24 In our study the cytokinemediated effect of albumin-fused rhGH is attenuated, likely due to reduced cytokine response to TV-1106 as compared to rhGH.…”
Section: Cytotoxicity Assessmentmentioning
confidence: 58%
See 2 more Smart Citations
“…Indirect, cytokine-mediated, suppression of mRNA and reduction in enzyme activity of CYP1A2 and CYP3A4 by plasma from blood treated with LPS were expected. 18,24 In our study the cytokinemediated effect of albumin-fused rhGH is attenuated, likely due to reduced cytokine response to TV-1106 as compared to rhGH.…”
Section: Cytotoxicity Assessmentmentioning
confidence: 58%
“…We developed a method for evaluation of biologics as direct and cytokine‐mediated determinants of hepatic biotransformation of xenobiotics. The assay is based on a treatment of whole blood with the biologic drug, followed by application of the resulted stimulated plasma to cultured hepatocytes . The CYPs selected for this study dominate xenobiotic metabolism in human liver and are suppressed by IL‐6 in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that the CYP3A4 mRNA response to INF‐α2a was attenuated by the addition of normal plasma (10% v/v) to the cell culture medium in our study. In a previous study, we observed that the addition of plasma (10%, v/v) from blood incubated with saline (2% v/v, 24 hour) to cell culture medium for 72 hour suppressed CYP3A4 mRNA in hepatocytes from three donors …”
Section: Discussionmentioning
confidence: 93%
“…Recent in vitro and in vivo studies have clearly shown that Kupffer cell activation is associated with a decrease in hepatic CYP expression and activity [6][7][8]. In addition, ROS and cytokines appear to cause a decrease in CYP expression resulting from an enhancement in CYP degradation and synthesis [9,10].…”
Section: Introductionmentioning
confidence: 97%